Conditions and strategies influencing sustainability of a community-based exercise program incorporating a healthcare-community partnership for people with balance and mobility limitations in Canada: A collective case study of the Together in Movement and Exercise (TIME™) program - Aravind, Gayatri; Graham, Ian D.; Cameron, Jill I.; Ploughman, Michelle; Salbach, Nancy M. (Frontiers in Rehabilitation Sciences, 2023)
Background: Community-based exercise programs delivered through healthcare-community partnerships (CBEP-HCPs) are beneficial to individuals with balance and mobility limitations. For the community to benefit, however, these programs must be sustained over time. Purpose: To identify conditions influencing the sustainability of CBEP-HCPs for people with balance and mobility limitations and strategies used to promote sustainability based on experiences of program providers, exercise participants, and caregivers. Methods: Using a qualitative collective case study design, we invited stakeholders (program providers, exercise participants, and caregivers) from sites that had been running a CBEP-HCP for people with balance and mobility limitations for ≥4 years; and sites where the CBEP-HCP had been discontinued, to participate. We used two sustainability models to inform development of interview guides and data analysis. Qualitative data from each site were integrated using a narrative approach to foster deeper understanding of within-organization experiences. Results: Twenty-nine individuals from 4 sustained and 4 discontinued sites in Ontario (n=6) and British Columbia (n=2), Canada, participated. Sites with sustained programs were characterized by conditions such as need for the program in the community, presence of secure funding or cost recovery mechanisms, presence of community partners, availability of experienced and motivated instructors, and the capacity to allocate resources towards program marketing and participant recruitment. For sites where programs discontinued, diminished participation and/or enrollment and an inability to allocate sufficient financial, human, and logistical resources towards the program affected program continuity. Participants from discontinued sites also identified issues such as staff with low motivation and limited experience, and presence of competing programs within the organization or the community. Staff associated the absence of referral pathways, insufficient community awareness of the program, and the inability to recover program cost due to poor participation, with program discontinuation. Conclusion: Sustainability of CBEP-HCPs for people with balance and mobility limitations is influenced by conditions that exist during program implementation and delivery, including the need for the program in the community, and organization and community capacity to bear the program’s financial and resource requirements. Complex interactions among these factors, in addition to strategies employed by program staff to promote sustainability, influence program sustainability.